Moldova Workforce Development : SABER Country Report 2013 - World Bank Group (World Bank, Washington, DC, 2015)
This report presents a comprehensive diagnostic of the Republic of Moldova s workforce development (WfD) policies and institutions. The analysis is based on a World Bank research tool created under the Systems Approach for Better Education Results (SABER) initiative and purposefully designed to provide systematic documentation and assessment of WfD policies and institutions. The SABER WfD benchmarking tool also aims to assist the government with the implementation of the VET Development Strategy in the context of international experience and global good practices.